Enhancements for the Search Functionality of an Open Source Email Client - Bhide, Aishwarya (My University, 2016)
Email is one of the most popular communication media in today'sworld. Various email clients are extensively used for professional as well as personal use. Many times the users of these email clients have to search for emails they have received or sent in the past. Although all email clients support search functionality, most of the widely used email clients do not have many advanced features. These features include query auto-correction, and showing emails related to an open email, which make email search more user-friendly and effective. The goal of this theses is to identify such limitations for one such email client, i.e. Thunderbird, and to create an add-on to address these limitations.
Keywords: Information Retrieval; Query correction